Engaging in online postgraduate education as means of professional learning - Broadley, Tania (University of Tasmania, 2011)
With enrolments in higher education becoming a competitive market, through the removal of caps in 2012, the equitable access to postgraduate education is raised. Postgraduate education, provided through higher education institutions, is an important aspect of career development for professionals. Professionals working outside of the metropolitan area are increasingly seeking postgraduate education opportunities that will be delivered online, at a distance. In this research study, data collected from the teaching profession, has culminated in a model that will ultimately improve access to professional learning. This research paper aims to highlight the important role that higher education providers play in the delivery of postgraduate education to professionals working in regional and remote areas of Australia. Although this paper focuses on the realm of education, the model of connectedness, where synchronous and asynchronus technlogies are used, can be adapted and applied to any profession that requires equitable access to professional learning.